ANALISIS PEMBELAJARAN IPA BERBASIS ETNOSAINS MELALUI PERMAINAN TRADISIONAL TARIK TAMBANG PADA MATERI GAYA DAN GERAK DI KELAS III SEKOLAH DASAR - Imit Desmita; Elfia Sukma; Inggria Kharisma (STKIP Subang, 2026)
This study aims to analyze the implementation of ethnoscience-based science learning through the traditional tug-of-war game on the topic of force and motion in elementary school. The ethnoscience approach integrates scientific concepts with local wisdom, making learning more contextual and closely related to students’ daily lives. The method used in this study is a literature review by examining various relevant sources related to ethnoscience, science learning, and the concepts of force and motion. The results of the review indicate that the concepts of force and motion are still difficult for students to understand because they are abstract and cannot be directly observed. These difficulties are influenced by students’ limited ability to relate concepts to real-life phenomena, a tendency to rely on rote learning, and a lack of direct learning experiences. The traditional tug-of-war game has the potential to be used as a learning medium because it contains concepts such as pulling force, frictional force, and force equilibrium, which can be observed directly. Through this activity, students can understand the concepts of force and motion more concretely because they are directly involved in the learning process. In addition, the ethnoscience approach can increase student engagement and motivation, as well as help them connect scientific concepts with their daily experiences. Therefore, ethnoscience-based science learning through the traditional tug-of-war game can be an effective alternative to improve conceptual understanding while also supporting the preservation of local culture.